Magnetic-Field-Stimulated Modification of Surface Charge and Defect Content in Silicon for Solar Energy Storage - Makara, V.A.; Steblenko, L.P.; Korotchenkov, O.A.; Nadtochiy, A.B.; Kalinichenko, D.V.; Kuryliuk, A.M.; Kobzar, Yu.L.; Krit, O.M. (Металлофизика и новейшие технологии, 2014)
The effect of a weak static magnetic field on the structure and charge state of silicon for solar energy storage is investigated. As found, the magnetic-fieldstimulated changes in the defect—impurity state and surface potential are reversible. В роботі досліджено вплив слабкого сталого магнітного поля на структуру та зарядовий стан кремнію для сонячної енергетики. Виявлено, що магнітостимульовані зміни дефектно-домішкового стану та поверхневого потенціалу мають зворотній характер. В работе исследуется влияние слабого постоянного магнитного поля на структуру и зарядовое состояние кремния для солнечной энергетики. Обнаружено, что магнитостимулированные изменения дефектно-примесного состояния и поверхностного потенциала носят обратимый характер.